A case study analysis of the role of resources in the teaching and learning of senior primary geography in the Northern Province - Khubana, Christopher Shonisani (Rhodes University, Faculty of Education, Department of Education, 1999)
The dynamic nature of Geography has meant that over the years it has undergone many changes. These changes - for example, in curricula, approaches and methods - have had a great impact on how Geography is taught and learned in schools. Learning theories on how children learn Geography are changing from behaviourism, in terms of which learners are regarded as passive recipients of knowledge in the form of facts, to socially constructivist theory, where learners learn by constructing their own knowledge. In the South African context this has meant moving away from the positivistic tendencies of the 1960s and 1970s, to constructivist practices embodied in the outcomes-based education envisaged for the 21st Century. These changes have impacted on the nature and use of resources. This research attempts to reveal teachers' and learners' perceptions of resources. In the previous curriculum, resources were largely limited to textbooks. In the new curriculum., our perception of resources has to become wider to encompass anything that can enhance teaching and learning. This study focuses on Grade 5 and 6 children in the Northern Province. In the intermediate phase, young children need a wide variety of resources. As we approach the 21 st Century, the information technology of media like computers and the Internet, together with traditional media and resources found in the environment, provide teachers and learners with great opportunities and a wide variety of choices. The study surveyed schools in the Northern Province, through a questionnaire. In order to understand the depth of the problem, three schools were selected for a case study. Data obtained from these studies were analysed and compared to determine trends and patterns regarding the availability or use of resources as teaching and learning aids. On the one hand the study highlights the severe lack of even basic infrastructure on which to develop a 'traditional' resource base and stresses the need for innovation and creativity (and dedication) among a teaching body which feels isolated and marginalised, while on the other hand this research has revealed teachers' desire and willingness to accept change and to adapt, given the necessary epistemological enforcement to effect change.
Keywords: Geography -- Study and teaching (Primary) -- South Africa; Geography -- Study and teaching (Primary) -- South Africa -- Northern Province